2021
DOI: 10.1002/sam.11512
|View full text |Cite
|
Sign up to set email alerts
|

Markov chain to analyze web usability of a university website using eye tracking data

Abstract: Web usability is a crucial feature of a website, allowing users to easily find information in a short time. Eye tracking data registered during the execution of tasks allow to measure web usability in a more objective way compared to questionnaires. In this work, we evaluated the web usability of the website of the University of Cagliari through the analysis of eye tracking data with qualitative and quantitative methods. Performances of two groups of students (i.e., high school and university students) across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Furthermore, Yuan employed a Markov Chain Model to enhance classroom teaching quality evaluation in universities, proposing an improved hybrid evaluation method and conducting comparative experiments to promote continuous improvement in teaching standards and overall educational quality [37]. Zammarchi, Frigau and Mola evaluated the web usability of a University in Italy website using eye tracking data, utilizing Markov chain analysis to study transitions between different areas of interest and suggesting areas for improvement in web usability based on fixation counts and the Markov chain analysis [38]. Paxinou et al investigated how virtual simulations enhance learning outcomes in science labs in a Greek University using a Markov Chain Model to predict students' performance, proposing that learners trained with virtual reality exhibit higher proficiency in conducting experiments compared to traditional methods [39].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Furthermore, Yuan employed a Markov Chain Model to enhance classroom teaching quality evaluation in universities, proposing an improved hybrid evaluation method and conducting comparative experiments to promote continuous improvement in teaching standards and overall educational quality [37]. Zammarchi, Frigau and Mola evaluated the web usability of a University in Italy website using eye tracking data, utilizing Markov chain analysis to study transitions between different areas of interest and suggesting areas for improvement in web usability based on fixation counts and the Markov chain analysis [38]. Paxinou et al investigated how virtual simulations enhance learning outcomes in science labs in a Greek University using a Markov Chain Model to predict students' performance, proposing that learners trained with virtual reality exhibit higher proficiency in conducting experiments compared to traditional methods [39].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Zammarchi et al [24] studied the web usability of the University of Cagliari's website using qualitative and quantitative methodologies to analyze eye-tracking data. They concluded that the information needed to complete the tasks could be easily acquired by students with limited prior experience with the website.…”
Section: Italymentioning
confidence: 99%
“…UWs had been well investigated for improvement of usability for all users in general [3,5,8,[10][11][13][14][15][16][17][18][19][20][21][22][23][24], such as students-lectures [4,13,25], people with disabilities [26], and even during the pandemic time [26][27][28][29]. However, there has been no holistic understanding and general trends based on the above literature on UW.…”
Section: Introductionmentioning
confidence: 99%
“…W artykule Markov chain to analyze web usability of a university website using eye tracking data [16] analizowano dane ruchu gałek ocznych w dwóch grupach: 56 osobowej grupie uczniów szkoły średniej oraz 66 osobowej grupie studentów, którzy wykonywali 10 zadań na stronie uniwersytetu Cagliari. Zebrane dane poddano analizie łańcuchem Markova oraz przedstawiono szczegółową procedurę przeprowadzenia takiego badania.…”
Section: W Artykule Research On Interactive Design Of Multilingual E-...unclassified